The lived experiences of registered nurses on structural empowerment and subsequent career advancement at a tertiary hospital in the Cape Metropole - Battle, Donna (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.